2011
DOI: 10.1016/j.jbi.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Data mining methods for classification of Medium-Chain Acyl-CoA dehydrogenase deficiency (MCADD) using non-derivatized tandem MS neonatal screening data

Abstract: Newborn screening programs for severe metabolic disorders using tandem mass spectrometry are widely used. Medium-Chain Acyl-CoA dehydrogenase deficiency (MCADD) is the most prevalent mitochondrial fatty acid oxidation defect (1:15,000 newborns) and it has been proven that early detection of this metabolic disease decreases mortality and improves the outcome. In previous studies, data mining methods on derivatized tandem MS datasets have shown high classification accuracies. However, no machine learning methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…Van den Bulcke et al 75 found that regression models performed better than C4.5 decision trees in identifying cases of modeling of medium-chain acyl-CoA dehydrogenase deficiency. They observed that decision trees were less robust, with changes in variable selection choices.…”
Section: Resultsmentioning
confidence: 99%
“…Van den Bulcke et al 75 found that regression models performed better than C4.5 decision trees in identifying cases of modeling of medium-chain acyl-CoA dehydrogenase deficiency. They observed that decision trees were less robust, with changes in variable selection choices.…”
Section: Resultsmentioning
confidence: 99%
“…The number of patients could vary from less than 20 patients [20,21,24,35,40,43,55] to more than 1000 patients [37,47,51,62,72,75]. As expected, the number of patients was usually more important for publications targeting more than one disease (groups 2 and 3) than for publications targeting one specific rare disease (group 1) ( Table 2).…”
Section: Methodsmentioning
confidence: 53%
“…Associations of different algorithms, such as fusion algorithms, were encountered in 2 studies [52,53]. Other authors reported using more traditional statistical modeling, such as regression [24] or decision trees [42,60]. The K Nearest Neighbors algorithm was used in 2 studies [51,72].…”
Section: Developed Modelsmentioning
confidence: 99%
“…Researchers have experimented with several ML models including probability [61, 70, 71], decision tree [58, 72, 73], discriminant [54, 70] and other types of ML models [52, 74, 75] to build phenotype categorization systems. In each case, the models essentially approach phenotyping as a classification or categorization problem with a positive class (the target phenotype) and a negative class (everything else).…”
Section: 3 Phenotype Algorithm Developmentmentioning
confidence: 99%